2020
DOI: 10.1002/adfm.202001924
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Roll‐to‐Roll Transfer and Doping of CVD‐Graphene Using Parylene for Ambient‐Stable and Ultra‐Lightweight Photovoltaics

Abstract: Large area graphene grown by chemical vapor deposition (CVD) has been the main focus of many researchers due to its vast areas of applications such as sensing or photovoltaics.Addressing the main challenges in transfer techniques such as Roll-to-Roll (R2R) process is a critical step for scaling up and commercialization of graphene. In this work, we employ a R2R transfer technique and improve the electrical properties of transferred graphene on flexible substrates using parylene as an interfacial layer. We depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 57 publications
(76 reference statements)
1
37
0
Order By: Relevance
“…Growing concerns for a natural environment drive innovation toward novel, clean energy sources, and storage devices. [ 1,2 ] Among them, cheap but efficient water‐splitting devices are being developed, and great hopes are being put into light‐enabled catalysts. The titania‐based electrode materials are especially looked at, because of their abundance, flexibility, and high stability within a wide pH range.…”
Section: Figurementioning
confidence: 99%
“…Growing concerns for a natural environment drive innovation toward novel, clean energy sources, and storage devices. [ 1,2 ] Among them, cheap but efficient water‐splitting devices are being developed, and great hopes are being put into light‐enabled catalysts. The titania‐based electrode materials are especially looked at, because of their abundance, flexibility, and high stability within a wide pH range.…”
Section: Figurementioning
confidence: 99%
“…have shown that adhesion energy between SLG and aromatic polymer of parylene‐C is 80% higher than that between SLG and non‐aromatic poly(ethylene vinyl acetate). [ 30 ] The favorable π–π interactions between SLG and PEI adhere the two components together, minimize their respective surface tensions, and mechanically reinforce the composite. [ 29,31,32 ] Second, the laminate structure contributes to mechanical enhancement, which is further strengthened by the strong adhesion between SLG and PEI.…”
Section: Figurementioning
confidence: 99%
“…2D materials, especially graphene, have attracted many researchers in the field of solar cells due to their exciting optoelectronic properties 33–35 . Since the scaling trend in the photovoltaic (PV) technology is moving toward lighter and thinner devices, the atomically thin structure and great flexibility of 2D materials make them ideal candidates for the next generation of thin film PVs 36,37 . For instance, monolayer graphene has shown great potential to be used as top and bottom electrodes in the thin film solar cells 38–41 .…”
Section: Introductionmentioning
confidence: 99%